PECS–ը որպես աուտիզմով երեխային արտասովոր իրավիճակներին նախապատրաստելու միջոց - Ավագյան, Արմենուհի (Զանգակ հրատ.)
Коммуникационная система с обменом картинок (PECS) является одной из методик альтернативной дополнительной коммуникации. Основная цель системы PECS – развитие навыков функциональной коммуникации у детей с аутизмом. PECS дает детям возможность общения не только в привычных, но и непривычных, нестандартных ситуациях. Это способствует положительным изменениям в поведении и в эмоционально–волевой сфере детей. В работе с детьми с ранним детским аутизмом обучению поведению в нестандартных, стрессовых ситуациях необходимо уделять специальное внимание. Picture Exchange Communication System (PECS) is considered as one of the alternative methods of additional communication. The primary goal of PECS system is the development of functional communication skills of children with autism. PECS gives the children an opportunity to communicate, not only in usual, but also in unusual, stressful situations. It promotes positive changes in behavior and emotional sphere of children. The experience has shown, that the children, who use PECS, are understood with ease by their surrounding people, as well as by their fellows, and the implication of pictures by parents in the process of information exchange improves its understanding.
Keywords: Ուսուցման և դասավանդման մեթոդիկա